Spawning Four-Year, ABET-Accreditable Programs in Cybersecurity from Existing Computer Science Programs in Thailand - Juneam, Nopadon; Greenlaw, Raymond (International Journal of Computing Sciences Research, 2024)
Purpose – Thailand faces many cybersecurity challenges. In the first few months of 2022 alone, there were over 300,000 cyber-attacks in the country, and annually the problem has gotten significantly worse. It is estimated that Thailand loses 286 billion US dollars per annum due to cybercrimes. These attacks include credit card fraud, phishing, ransomware, scamming, information, and identity theft, business email compromises, child pornography, intellectual property infringements, cyberstalking and harassment, denial of service, botnets, fake news, and stolen funds. To defend against cyber criminals, well-trained professionals in cybersecurity are needed. By 2025, there is an expected shortfall of over four million cybersecurity workers globally. We examine what it would take to spawn an accreditable four-year curriculum in cybersecurity from a typical Thai Bachelor of Science in Computer Science. At present, there are few university programs in Thailand dedicated to cybersecurity. We hope this work inspires educational institutions to develop quality four-year degrees in cybersecurity, with the goals of meeting workforce demands, reducing cybercrime, and promoting Thailand as a viable and healthy place to conduct e-business. Method – The paper employs expert analysis to forge an accreditable program in cybersecurity from a computer science program. Results – The authors describe an ABET-accreditable program in cybersecurity and show how to develop it in a step-by-step manner. Conclusion – An ABET-accreditable program in cybersecurity can be spawned from a computer science program with relatively few additional courses and modifications while placing more emphasis on ABET's crosscutting concepts. Recommendations – Institutions that are interested in developing four-year cybersecurity programs can begin crafting them in the manner described in this work. Research Implications – Cybersecurity professionals can be developed. Practical Implications – New quality cybersecurity programs can be developed promptly. Social Implications – There will be more qualified professionals to help fight cybercriminals.